FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT FINANCIAL LITERACY INVESTOR DI KOTA DENPASAR PADA BURSA EFEK INDONESIA - Kirana Dewi, Ni Made Wida Puspita; Ayuningsasi, Anak Agung Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.12.TAHUN.2021DO - 10.24843/EEB.2021.v10.i12.p03, 2021)
This study aims to analyze the effect of education level, gender, income, and marital status simultaneously and partially on the financial literacy level of investors in the capital market in Denpasar City. The research population is the entire community of Denpasar City who invests in the capital market, with a total sample of 100 respondents who were determined based on accidental sampling of a snowball combination. The research method uses primary data (observation, structured interviews, and in-depth interviews). The data analysis technique used was multiple linear regression with those analyzed by the SPSS program. The results showed that, 1) simultaneously the variables of education, gender, income, and marital status had a significant effect on the level of financial literacy of investors in the capital market in Denpasar City; 2) partially education and income variables have a positive and significant effect on the level of financial literacy of investors in the capital market in Denpasar City, the level of financial literacy of capital market investors in Denpasar City, which is male is greater than that of female, and financial level the literacy of capital market investors in Denpasar City who are married is greater than those who are not married.